1992
DOI: 10.1104/pp.99.4.1520
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an Anaerobically Induced Alanine Aminotransferase from Barley Roots

Abstract: Alanine aminotransferase (AlaAT, EC 2.6.1.2) is an enzyme that is induced under anaerobic conditions in cereal roots. In barley (Hordeum vulgare L.) roots, there are a number of isoforms of AlaAT. We have identified the anaerobically induced isoform and have purified it to homogeneity. The isolation procedure involved a two-step ammonium sulfate precipitation, gel filtration, ionexchange chromatography, and chromatofocusing. The enzyme was purified approximately 350-fold to a specific activity of 2231 units/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 26 publications
3
57
0
Order By: Relevance
“…GABA and succinate semialdehyde, respectively) inhibit background reactions. For example, Good and Muench (1992) demonstrated that 1 mM GABA inhibits g1utamate:pyruvate transaminase by 24%. Furthermore, accumulation of succinate semialdehyde is known to be toxic to cells (Hearl and Churchich, 1984) and may possibly inhibit other dehydrogenases.…”
Section: Resultsmentioning
confidence: 99%
“…GABA and succinate semialdehyde, respectively) inhibit background reactions. For example, Good and Muench (1992) demonstrated that 1 mM GABA inhibits g1utamate:pyruvate transaminase by 24%. Furthermore, accumulation of succinate semialdehyde is known to be toxic to cells (Hearl and Churchich, 1984) and may possibly inhibit other dehydrogenases.…”
Section: Resultsmentioning
confidence: 99%
“…The pyruvate enters a lactate dehydrogenase-catalyzed reaction with NADH to produce lactate and NAD + . The AlaAT activity was measured as the decrease in absorbance resulting from the consumption of NADH at 340 nm (Griffith and Vance, 1989;Good and Muench, 1992). The reaction buffer consisted of 15 mM α-oxoglutarate, 0.15 mM NADH, 0.5 M l-alanine, and 5 units of lactate dehydrogenase in 50 mM Tris-HCl buffer (pH 7.5), and the reaction was initiated by adding 100 µL of enzyme extract.…”
Section: Alanine Aminotransferase (Alaat) and Aspartate Aminotransfermentioning
confidence: 99%
“…The activity of Alanine Transaminase (AlaT; EC 2.6.1.2) was quantified as described by Good and Muench (1992). The reaction mixture was 100 mmol L -1 Tris-HCl (pH 8.0), 0.2 mmol L -1 NADH, 20 mmol L -1 L-Alanine, 1 unit of Lactate dehydrogenase, 30 µL of the enzyme extract, and 10 mmol L -1 2-oxyglutarate (Start).…”
Section: Hypoxia-responsive Enzyme Activitymentioning
confidence: 99%